Analisis Keterampilan dan Pengetahuan Sumber Daya Manusia dalam Meningkatkan Efisiensi Produksi Rumput Laut di Sumenep - Rokhmani, Kholilur; Afifah, Zainiyatul; Kuswinaro, Mudji (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to determine the human resource competencies needed to improve seaweed production efficiency and to examine how human resource knowledge plays a role in increasing production efficiency in Sumenep. This study uses a qualitative approach. Data were obtained through interviews, observations, and documentation from farmers and production managers. The results showed that to increase seaweed production yields, good technical and managerial skills are needed, as well as knowledge of effective cultivation techniques. Furthermore, it was proven that improving HR skills through continuous training increases the welfare and productivity of farmers. This study found that more inclusive training programs are needed so that human resources in seaweed cultivation in Sumenep can be maximized. Keywords: Human Resources Knowledge, Production Efficiency, Skills